Uma análise dos elementos em comum entre as práticas do consumo sustentável e do minimalismo - Oliveira, Rafaela Melo de (2022)
Minimalism and sustainable consumption can contribute to a process of formation of a new conscience based on new consumption habits, since many socio-environmental problems are consequences of standards imposed by the market and the means of communication. Thus, the general objective of this research is to analyze how the minimalism relates to the practice of sustainable consumption. During the execution of this research, the world was surprised by the pandemic of the new coronavirus, which generated changes in people's routine due to the restriction measures adopted to contain the spread. For Therefore, the context of the pandemic was included in the study. A qualitative research was carried out and interpretivist. The research subjects are consumers who have adopted the lifestyle minimalist and were selected through social networks Whatsapp or Instagram and through recommendation. The intention of this research is to make a study analyzing the practices of minimalism and sustainable consumption in order to compare the elements of practices in these different groups. The survey was conducted through an open interview and the questions are based on in the literature review of sustainable consumption, theories of practice and minimalism. Were interviewed 10 subjects. The answers were analyzed according to the content analysis of Bardin. The categories were determined through the analysis of minimalism practices and sustainable consumption, bringing the material elements, meaning and practical knowledge. So, it is understood that minimalism is multifaceted and is about rationalizing the amount of goods and the level of consumption, making it possible to identify it as a practice under construction. It can be related to sustainable consumption in a way that minimalists attribute meanings, identify material elements and present skills and knowledge that are often mixed with those practiced in sustainable consumption. However, despite the similarities found, the meaning of the subcategory is not always the same. Regarding consumption during the pandemic, frustration with restricting the experience of the consumption, as well as the growth of digital consumption. Thus, through this work, it is possible to contribute to the management literature and studies on minimalism, in the field of sustainable consumption. In addition to being valuable to consumers, who will get to know new ways to achieve well-being outside consumption and guide organizations towards development of commercial and marketing strategies, which aim to capture this type of consumer.